2022
DOI: 10.3390/ijms23158665
|View full text |Cite
|
Sign up to set email alerts
|

Role of a ZF-HD Transcription Factor in miR157-Mediated Feed-Forward Regulatory Module That Determines Plant Architecture in Arabidopsis

Abstract: In plants, vegetative and reproductive development are associated with agronomically important traits that contribute to grain yield and biomass. Zinc finger homeodomain (ZF-HD) transcription factors (TFs) constitute a relatively small gene family that has been studied in several model plants, including Arabidopsis thaliana L. and Oryza sativa L. The ZF-HD family members play important roles in plant growth and development, but their contribution to the regulation of plant architecture remains largely unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…NnZHD9 is a member of the Zinc‐Finger homeodomain (ZF‐HD) family and contains a highly conserved HD domain (Zhou et al., 2021). Several studies on model plants have shown that ZF‐HD is specifically expressed in flower tissues and plays an important role in young flowers (He et al., 2022; Lee et al., 2022). Members of the ZF‐HD gene family often act as upstream regulators of plant growth, development and abiotic stress tolerance (Shi et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…NnZHD9 is a member of the Zinc‐Finger homeodomain (ZF‐HD) family and contains a highly conserved HD domain (Zhou et al., 2021). Several studies on model plants have shown that ZF‐HD is specifically expressed in flower tissues and plays an important role in young flowers (He et al., 2022; Lee et al., 2022). Members of the ZF‐HD gene family often act as upstream regulators of plant growth, development and abiotic stress tolerance (Shi et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger homeodomain TFs (ZF-HD TFs) with notably HB34 have been identified as regulators of plant architecture. Indeed, HB34 positively regulates SPL10 while repressing MIR157d thus forming a feed-forward loop (FFL) (Lee et al, 2022). FFL are three-component patterns where a TF regulates the two other components that are already involved in regulatory interactions (Figure 2).…”
Section: Mirna Integration In Developmental Gene Regulatory Networkmentioning
confidence: 99%
“…Among the factors accounting for plant leaf rolling are proteins related to cell wall, particularly secondary cell wall biosynthesis or formation (Zhu et al, 2022b;De Souza et al, 2023). It has recently been discovered that SQUAMOSA PROMOTER BINDING PROTEIN-LIKE 10 (SPL10), which is characterized to be functionally associated with cell wall development (Bascom, 2023), is a direct downstream target of HB34 (Lee et al, 2022). Collectively, HB34 in our study thus may participate in negatively controlling cell wall development and thereby affect leaf rolling and (possibly) lengthening during PSD, which may consequently lead to enhanced transpiration and thereafter water loss.…”
Section: Genetic Factors Coordinate the Phenotypic Responses To Combi...mentioning
confidence: 72%